The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.15850/amj.v3n4.954
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude on Febrile Seizure among Mothers with Under-Five Children

Abstract: Background: Febrile seizures frequently occur in children under 5 years old and usually create fear and anxiety among parents. Poor understanding of febrile seizure among parents contributes to mismanagement of seizure. The objective of this study was to identify the knowledge and attitude on febrile seizure among mothers of under five children. Methods: This descriptive community-based survey comprised of 96 mothers with under 5 children who were chosen through randomization. This survey was, conducted in Heg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
1
8
1
Order By: Relevance
“…Twenty-five (15.2%) respondents thought that febrile convulsion is due to evil spirit. This has been reported in other studies within and outside Nigeria [14][15][16][17][18]. Anigilaje et al reported that subjects attributed 'angry gods' (51.8%), evil spirit (49.0%), constipation (36.8%) and black blood (0.6%) to be causes of febrile convulsion [18].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Twenty-five (15.2%) respondents thought that febrile convulsion is due to evil spirit. This has been reported in other studies within and outside Nigeria [14][15][16][17][18]. Anigilaje et al reported that subjects attributed 'angry gods' (51.8%), evil spirit (49.0%), constipation (36.8%) and black blood (0.6%) to be causes of febrile convulsion [18].…”
Section: Discussionsupporting
confidence: 65%
“…Nyaledzigbor et al in a study in Ghana also reported that majority (70%) of the mothers believed that febrile convulsion occurs as a result of high fever [16]. Sahida et al also gave a similar (61%) report among mothers in Indonesia [17].…”
Section: Discussionmentioning
confidence: 89%
“…One study found that although knowledge and attitude regarding FS might be useful, the knowledge and attitude toward outcome and what to do during FS events are still low. 28 However, our study found that parents with higher education had a better QoL with their children. One plausible explanation is that parents who had higher education had a better understanding of the prognosis and tend to worry less.…”
Section: Discussioncontrasting
confidence: 56%
“…Febrile convulsion was attributed to social determinants of health speci cally poor sanitation, nutrition, and childcare practices. Poor environment during pregnancy for instance is a known determinant of febrile convulsion [20]. On nutrition, particularly phlegm accumulation, most mothers attributed the cause of FC to phlegm in Ghana [6].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the perceptions and beliefs about the causes, and by extension, diagnosis of all forms or types of illnesses are underpinned by these three main dimensions, or their constellations [18]. For instance, some local communities and people have the perceptions that diseases could be contracted from genetic factors [5,19], poor dietary practices and unacceptable social behaviour [20], and curses or witchcraft attacks [6,9]. From a theoretical perspective, the health belief model has been applied.…”
Section: Contextual and Theoretical Issuesmentioning
confidence: 99%